A new amide alkaloid induces the apoptosis of human melanoma A375 cells via inhibition of the STAT3 signaling pathway. (30th November 2022) - Wang, Ru; Yang, Bo; Zhang, Beibei; Zhang, Qinqin; Cao, Bing; Jia, Jufang; Liu, Meng; Guo, Pengli; Zhang, Yuhan; Li, Xiaokun; Zheng, Xiaoke; Feng, Weisheng
Abstract : A new amide alkaloid (ZYL-01) can inhibit the activity of A375 cells by inducing cell apoptosis via inhibiting STAT3 signaling. Abstract : Melanoma is the deadliest invasive skin cancer, posing a serious threat to human health. Emerging evidence has shown that STAT3 is a major oncogene in melanoma and validated as a target for melanoma therapy. In this study, we synthesized a new amide alkaloid, ( R )-2-(butylamino)- N -(4-((4-methylpiperazine-1-yl) methyl) phenyl)-4-(piperidine-3-ylamino) pyrimidine-5-carboxamide (ZYL-01). AG490 (the antagonist of STAT3) and the human melanoma A375 cells and A375 cells transfected with the STAT3C expression construct (A375-STAT3-3C) or with an empty vector (A375-STAT3-NC) are used to investigate the effects of ZYL-01 treatment of human melanoma A375 cells and determine the relevant mechanisms. Our results showed that ZYL-01 significantly reduced the A375 cell index, inhibited A375 cell proliferation and migration capacity, reduced the levels of MMP and increased the levels of ROS, Ca 2+, and apoptosis in A375, A375-STAT3-3C and A375-STAT3-NC cells in a dose-dependent manner. The effect of AG490 was more significant compared to cells without AG490, and the effect of A375-STAT3-NC cells was more significant than A375-STAT3-3C cells. ZYL-01 markedly increased the expression of Bax and cleaved caspase-3 and reduced Bcl-2 and p-STAT3. In conclusion, our results suggest that ZYL-01 could inhibit the activity of A375 cells by inducing cells apoptosis via inhibiting the STAT3 signaling pathway.